Outdoor cultivation of Picochlorum sp. in a novel V-shaped photobioreactor on the Caribbean island Bonaire - Chin-On, Rocca; de Boer, Mila; van de Voort, Cas; Camstra, Juliëtte; Barbosa, Maria; Wijffels, René H.; Janssen, Marcel (Frontiers in Bioengineering and Biotechnology, 2024)
Microalgae are a promising renewable feedstock that can be produced on non-arable land using seawater. Their biomass contains proteins, lipids, carbohydrates, and pigments, and can be used for various biobased products, such as food, feed, biochemicals, and biofuels. For such applications, the production costs need to be reduced, for example, by improving biomass productivity in photobioreactors. In this study, Picochlorum sp. (BPE23) was cultivated in a prototype of a novel outdoor V-shaped photobioreactor on Bonaire (12°N, 68°W). The novel photobioreactor design was previously proposed for the capture and dilution of sunlight at lowlatitude locations. During several months, the biomass productivity of the local thermotolerant microalgae was determined at different dilution rates in continuous dilution and batch dilution experiments, without any form of temperature control. Reactor temperatures increased to 35-45°C at midday. In the continuous dilution experiments, high average biomass productivities of 28-31 g m -2 d -1 and photosynthetic efficiencies of 3.5-4.3% were achieved. In the batch dilution experiments, biomass productivities were lower (17-23 g m -2 d -1 ), as microalgal cells likely experienced sudden light and temperature stress after daily reactor dilution. Nonetheless, dense cultures were characterized by high maximum photosynthetic rates, illustrating the potential of Picochlorum sp. for fast growth under outdoor conditions.